Learning Model Problem-Based Learning in Increasing Learning Concentration of Elementary School Students in Integrated Thematic Lessons Reviewing from Learning Outcomes - Ernawati (Universitas Negeri Malang, 2022)
This study aims to determine how the learning outcomes of the Problem-Based Learning (PBL) learning model increase the concentration of elementary school students on integrated thematic subjects. The experimental method is used for research. The mean post-test value for the experimental class is 83.80 percent and the mean post-test for the control class is 78.80 percent, indicating that student learning outcomes are visible. The experimental class has a gain index g greater than 0.69, while the control class has a gain index g greater than 0.59. The results of the t-test indicate that Sig and t-count (4.388) are greater than T-table (2.052). 2-tailed) 0.05 or 0.014, indicating that students at SDN Hikmah II Yapis, Jayapura City, Papua Province are more concentrated in learning integrated thematic subjects thanks toProblem-Basedd Learning model. Penelitian ini bertujuan untuk menentukan bagaimana hasil penerapan model pembelajaran Problem Based Learning (PBL) dapat meningkatkan konsentrasi siswa sekolah dasar pada pembelajaran tematik. Metode yang digunakan dalam penelitian adalah metode eksperimental. Nilai rata-rata postes kelas eksperimen adalah 83,80 persen dan rata-rata posttest untuk kelas kontrol adalah 78,80 persen, menunjukkan bahwa terdapat perbedaan hasil belajar siswa. Kelas eksperimental mendapatkan indeks g lebih besar dari 0,69, sementara kelas kontrol mendapatkan indeks g lebih besar dari 0,59. Hasil dari uji t-test menunjukkan bahwa Sig dan t-count (4,388) lebih besar daripada T-table (2,052). 2-tailed) 0,05 atau 0,014, menunjukkan bahwa para siswa di SDN Hikmah II Yapis, kota Jayapura, provinsi Papua lebih berkonsentrasi dalam mempelajari mata pelajaran dalam tematik dengan penggunaan model Problem Based Learning.